2012
DOI: 10.1517/17425255.2012.657626
|View full text |Cite
|
Sign up to set email alerts
|

Cytochrome P450 variations in different ethnic populations

Abstract: Racial/ethnic differences in metabolic phenotype can be explained by differences in SNP distribution. However, overlap in substrate specificity, linkage disequilibrium and previously unidentified SNPs have made phenotypic characterization difficult for CYP3A4/5 and 2C8/9. Studies utilizing newly identified, highly prevalent, racially stratified SNPs and their impact on CYP isoform-specific metabolism will provide new answers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
170
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 244 publications
(175 citation statements)
references
References 81 publications
2
170
0
3
Order By: Relevance
“…SNPs have been identified that may result in variant CYP450 enzyme expression and/or activity (McGraw and Waller, 2012). In this study, we chose representative alleles of CYP1A2, among which CYP1A2*1F is reported to be associated with increased activity, while the CYP1A2*1C, CYP1A2*2, CYP1A2*7, and CYP1A2*11 variants are associated with decreased activity of the CYP1A2 gene (Zhou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…SNPs have been identified that may result in variant CYP450 enzyme expression and/or activity (McGraw and Waller, 2012). In this study, we chose representative alleles of CYP1A2, among which CYP1A2*1F is reported to be associated with increased activity, while the CYP1A2*1C, CYP1A2*2, CYP1A2*7, and CYP1A2*11 variants are associated with decreased activity of the CYP1A2 gene (Zhou et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the Caucasian population, both Asian and African populations have lower CYP1A2 activities (39). Fourteen percent of Japanese people and 5% of Chinese people were found to be PMs (17,27).…”
Section: Cyp1a2mentioning
confidence: 99%
“…The distribution of common variant alleles of CYP2C19 has been found to vary among different ethnic groups. The PM phenotype is more prevalent in the Asian population and less in Caucasian and African populations (please see below) (17). The PM phenotype of CYP2C19 is inherited as an autosomal recessive trait (28,29) (Table 2).…”
Section: Cyp2c19mentioning
confidence: 99%
“…Furthermore, the frequencies of CYP2C9*3 allele were similar between the Vietnamese-Koreans and Africans (3.2% and 0.5-2.3%) but Caucasians exhibited high proportion of this allele (3.3-17%). This suggests that Vietnamese-Koreans have less clinical significance caused by CYP2C9 genotype than Caucasian population [32]. Second, in the distribution of CYP2C19, the Vietnamese-Koreans have low frequency of *17 (2.0%) compared to Caucasians and African-Americans (~20% and 17-18%).…”
Section: Transl Clin Pharmacolmentioning
confidence: 96%